Patient perspective of ward rounds in Swiss internal medicine departments: a mixed-methods study (Swiss Medical Weekly, 2025)
BACKGROUND: Ward rounds carried out by interprofessional teams are an important element of patient-centred care in the field of internal medicine. This quantitative and qualitative study aimed to assess patient satisfaction with interprofessional ward rounds.METHODS: This mixed-methods observational study evaluated patient satisfaction with ward rounds in a hospital setting. A total of 211 hospitalised patients from four different hospitals were assessed between 25 August and 8 September 2023. Quantitative data were collected using a visual analogue scale (VAS) from 0 to 10 with satisfaction scores at or below the median VAS defined as the primary endpoint. A median split was applied to categorise patients into groups for comparison. We examined associations between ward round-related factors and satisfaction. Additionally, a qualitative assessment was conducted using open-ended interviews to explore patients’ perception of ward rounds. The study adhered to standards for reporting qualitative research.RESULTS: Of the 211 patients analysed (participation rate 59.3%), the median satisfaction score was 8 points. Lower satisfaction was significantly less frequent among patients who reported high comprehensibility (i.e. information was understandable) of their current medical situation (adjusted odds ratio [OR] 0.55, 95% confidence interval [CI] 0.45–0.69; p